2014
DOI: 10.1186/1556-276x-9-396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiwalled carbon nanotubes and triclocarban on several eukaryotic cell lines: elucidating cytotoxicity, endocrine disruption, and reactive oxygen species generation

Abstract: To date, only a few reports about studies on toxic effects of carbon nanotubes (CNT) are available, and their results are often controversial. Three different cell lines (rainbow trout liver cells (RTL-W1), human adrenocortical carcinoma cells (T47Dluc), and human adrenocarcinoma cells (H295R)) were exposed to multiwalled carbon nanotubes, the antimicrobial agent triclocarban (TCC) as well as the mixture of both substances in a concentration range of 3.13 to 50 mg CNT/L, 31.25 to 500 μg TCC/L, and 3.13 to 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 139 publications
(183 reference statements)
0
18
1
1
Order By: Relevance
“…Nonetheless, whether CNTs are inherently cytotoxic at any organic systems has yet to be definitely proven. Simon et al [26] tested levels of MWNT cytotoxicity in different eukaryotic cell lines and concluded that exposition to the compound rendered neither cytotoxicity nor endocrine disruption to any of them. Furthermore, it is widely accepted that functionalization of CNTs reduces their toxicity and also increases biocompatibility [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, whether CNTs are inherently cytotoxic at any organic systems has yet to be definitely proven. Simon et al [26] tested levels of MWNT cytotoxicity in different eukaryotic cell lines and concluded that exposition to the compound rendered neither cytotoxicity nor endocrine disruption to any of them. Furthermore, it is widely accepted that functionalization of CNTs reduces their toxicity and also increases biocompatibility [27].…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis to explain how the association of MWNT has so dramatically changed the immunogenic potential of the very same protein is that the functionalization of the DENV3E with MWNT may have led to a differential profile of antigenic presentation. Moreover, it has been shown that ƒ-CNTs have immunostimulatory properties and are able to induce the production of cytokines [26, 34]. Thus, the increased neutralizing antibody titers could have been a result of CNT-driven immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…A cell free reactive oxygen species (ROS) detection was conducted according to the procedure by Simon et al (2014) and Rushton et al (2010). This assay quantifies the amount of ROS in the medium whereas other assays measure the ROS within animal cells.…”
Section: Cell Free Reactive Oxygen Species (Ros) Detectionmentioning
confidence: 99%
“…Following delivery of anticancer drugs to target cells, CNTs are transported by blood to the heart, liver, lungs, kidneys, 100 brain, 101 embryo 102 and other organs ( Figure 2), producing oxidative stress and causing cellular damage. 103,104 Due to their specific surface properties and small size, even purified CNTs can cause toxicity to tissues or organs. For example, after 48 h co-culture of HeLa cells with 100 μg/mL untreated and purified SWCNTs by Tsuji and colleagues, 70% HeLa cells in the untreated group displayed apoptosis relative to 40% HeLa cells in the purified group, supporting the theory that CNTs are inherently toxic irrespective of the purity of the preparation.…”
Section: Toxic Manifestations Of Anti-tumor Drug Carrier Cntsmentioning
confidence: 99%